2015
DOI: 10.5796/electrochemistry.83.715
|View full text |Cite
|
Sign up to set email alerts
|

The Electrochemical Assembly of ZnO Nanostructures Through the Modification and Influence of Soft Templates in Reverse Micelle

Abstract: Electrochemical assembly of ZnO nanostructures in reverse micelle through the modification and influence of the soft template have been successfully performed. It has been found that the morphologies of ZnO are greatly influence by the added Li + or K + rather than current density. The reason is that alkali metal ions will accumulate at the interface of the cathode/solution and influence the flexibility of soft template. As can be seen, only random sheet can be obtained without alkali metal ions while differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It was reported that alkali metal ions behave as templating agents. 55 Herein, Na + ions lead to a more facile templating effect via coordination with a 5-membered imidazole ring of ionic liquid 1-butyl-3-methylimidazolium bromide 56 compared to Li + and K + ions. It led to the highest surface area, pore volume and pore diameter of the Fe 2 O 3 -Na sample.…”
Section: Electrospray Ionization (Esi)-mass Spectrometry (Ms) Studymentioning
confidence: 99%
“…It was reported that alkali metal ions behave as templating agents. 55 Herein, Na + ions lead to a more facile templating effect via coordination with a 5-membered imidazole ring of ionic liquid 1-butyl-3-methylimidazolium bromide 56 compared to Li + and K + ions. It led to the highest surface area, pore volume and pore diameter of the Fe 2 O 3 -Na sample.…”
Section: Electrospray Ionization (Esi)-mass Spectrometry (Ms) Studymentioning
confidence: 99%